2019
DOI: 10.1093/mnras/stz2708
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic 26Al emission from galactic-scale superbubble simulations

Abstract: Emission from the radioactive trace element 26Al has been observed throughout the Milky Way with the COMPTEL and INTEGRAL satellites. In particular, the Doppler shifts measured with INTEGRAL connect 26Al with superbubbles, which may guide 26Al flows off spiral arms in the direction of Galactic rotation. In order to test this paradigm, we have performed galaxy-scale simulations of superbubbles with 26Al injection in a Milky Way-type galaxy. We produce all-sky synthetic γ-ray emission maps of the simulated galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 57 publications
8
26
0
Order By: Relevance
“…A large-scale simulation had indicated that the 26 Al mass in the Galaxy could be even lower [49]. On the other hand, other Galactic-scale hydrodynamic simulations with 26 Al sources distributed along spiral arms reproduce the INTEGRAL observations with a steady-state mass of ∼4 M , values between 2.5 and 6 M being consistent with these simulations [51]. It remains to be seen how morphology improvements from imaging as well as simulation work will refine the role of nearby and intermediate-distance clusters.…”
Section: The Mass Of 26 Al In the Galaxysupporting
confidence: 69%
See 2 more Smart Citations
“…A large-scale simulation had indicated that the 26 Al mass in the Galaxy could be even lower [49]. On the other hand, other Galactic-scale hydrodynamic simulations with 26 Al sources distributed along spiral arms reproduce the INTEGRAL observations with a steady-state mass of ∼4 M , values between 2.5 and 6 M being consistent with these simulations [51]. It remains to be seen how morphology improvements from imaging as well as simulation work will refine the role of nearby and intermediate-distance clusters.…”
Section: The Mass Of 26 Al In the Galaxysupporting
confidence: 69%
“…Massive star ejecta as traced by 26 Al therefore may recycle to the next generation of stars on a long way over the halo of the Milky Way on timescales likely exceeding 10 Myrs. Recent galaxy-scale hydrodynamics simulations with 26 Al ejection show that the 26 Al scale height is sensitive to the assumed galaxy structure, clustering of star formation as well the gas density in the lower halo [49,50,51]. With realistic assumptions, scale heights of about 2 kpc near the solar radius are found [51], similar to values derived from the INTE-GRAL data [50].…”
Section: Al Decay Within Superbubblessupporting
confidence: 65%
See 1 more Smart Citation
“…The simulation we analyse here have been presented in detail in Rodgers-Lee et al (2019). In short, it is a set of 3D hydrodynamic simulations of the interstellar medium of an isolated disc galaxy set in a gravitational potential that represents the static dark matter halo, stellar bulge, disc and rotating spiral arms.…”
Section: Simulationsmentioning
confidence: 99%
“…The background model is inferred from the data in the background region of the 2016 flight (Figure 1). Although high-latitude emission at 1.8 MeV is recently discussed in the literature [16,17], COSI observations of these regions are dominated by instrumental background radiation and were thus deemed adequate for estimating the background contribution.…”
Section: Background Modelmentioning
confidence: 99%